Improving Tracheostomy Decannulation Rate in Trauma Patients. (July 2019) - Farrell, Michael S.; Gillin, Thomas M.; Emberger, John S.; Getchell, John; Caplan, Richard J.; Cipolle, Mark D.; Bradley, Kevin M.
Abstract : Objectives: Identify the effect of a multidisciplinary tracheostomy decannulation protocol in the trauma population. Design: Single-center retrospective review. Setting: American College of Surgeons level 1 trauma center; large academic associated community hospital. Patients: Adult trauma patients who required a tracheostomy. Interventions: A tracheostomy decannulation protocol empowering respiratory therapists to move patients toward tracheostomy decannulation. Measurements Main Results: Tracheostomy decannulation rate, time to tracheostomy decannulation, length of stay, and reintubation and recannulation rates. A total of 252 patients met inclusion criteria during the study period with 134 presenting after the tracheostomy decannulation protocol was available. Since the tracheostomy decannulation protocol was implemented, patients managed by the tracheostomy decannulation protocol had a 50% higher chance of tracheostomy decannulation during the hospital stay ( p < 0.001). The time to tracheostomy decannulation was 1 day shorter with the tracheostomy decannulation protocol ( p = 0.54). There was no difference in time to discharge after ventilator liberation ( p = 0.91) or in discharge disposition ( p = 0.66). When comparing all patients, the development of a tracheostomy decannulation protocol, regardless if a patient was managed by the tracheostomy decannulation protocol, resulted in an 18% higher chance of tracheostomy decannulation ( p = 0.003). Time to tracheostomy decannulation was 5 days shorter in the postintervention period ( p = 0.07). There was no difference in discharge disposition ( p = 0.88) but the time to discharge after ventilator liberation was shorter post protocol initiation ( p = 0.04). Conclusions: In a trauma population, implementation of a tracheostomy decannulation protocol significantly improves tracheostomy decannulation rates during the same hospital stay. A larger population will be required to identify patient predictive factors for earlier successful tracheostomy decannulation.